2016
DOI: 10.1016/j.jconrel.2015.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced FcRn-dependent transepithelial delivery of IgG by Fc-engineering and polymerization

Abstract: Monoclonal IgG antibodies (Abs) are used extensively in the clinic to treat cancer and autoimmune diseases. In addition, therapeutic proteins are genetically fused to the constant Fc part of IgG. In both cases, the Fc secures a long serum half-life and favourable pharmacokinetics due to its pH-dependent interaction with the neonatal Fc receptor (FcRn). FcRn also mediates transport of intact IgG across polarized epithelial barriers, a pathway that is attractive for delivery of Fc-containing therapeutics. So far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 100 publications
6
30
0
Order By: Relevance
“…198 Similarly, aggregates of thermally stressed IgG1 have enhanced affinity for FcRn, while immune-complexed and hexamerized IgG1 have enhanced FcRnmediated transepithelial transport. 199,200 For CD40 antibodies, agonism is generally dependent on FcgRIIb-mediated crosslinking. However, covalent multimers of mouse IgG2a were shown to activate CD40 in a FcgR-independent manner, allowing for increased survival in a mouse lymphoma model.…”
Section: Antibody Multimerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…198 Similarly, aggregates of thermally stressed IgG1 have enhanced affinity for FcRn, while immune-complexed and hexamerized IgG1 have enhanced FcRnmediated transepithelial transport. 199,200 For CD40 antibodies, agonism is generally dependent on FcgRIIb-mediated crosslinking. However, covalent multimers of mouse IgG2a were shown to activate CD40 in a FcgR-independent manner, allowing for increased survival in a mouse lymphoma model.…”
Section: Antibody Multimerizationmentioning
confidence: 99%
“…Attachment of the IgM tailpiece to the IgG C-terminus is another hexamerization approach that allows for enhanced binding to Fc-binding proteins. 200,203 Depending on structure and context, these multimerizing antibodies may be useful for both potentiating and inhibiting the immune functions of complement and FcRs.…”
Section: Antibody Multimerizationmentioning
confidence: 99%
“…Interestingly, this FcRn-mediated enhancement of IgG1 half-life improved antitumor activity of Fc-engineering antibodies in mice(Zalevsky et al, 2010), suggesting that at least in these mice cancer models, increased drug exposure through half-life extension can enhance efficacy and enables less frequent drug dosing(Sockolosky and Szoka, 2015). Very recently, Foss and colleagues have made a thorough comparison on how IgG and different Fc-fusion formats are transported across human epithelial cells(Foss et al, 2016).The authors confirmed that transepithelial delivery is strongly dependent on the format of the ligands and on the appropriate pH conditions, and observed enhanced transport rates upon Fcengineering or polymerization, as compared with intact IgG1(Foss et al, 2016). Furthermore, a number of other mutations to the IgG Fc-domain that alter the pH-dependent binding have been extensively described and reviewed(Chen and Balthasar, 2012;Kuo and Aveson, 2011;Rath et al, 2015;Sockolosky and Szoka, 2015).Altogether, these findings validated the tremendous impact of the Fc engineering strategies, since the several mutations demonstrated the simultaneous modulation of the serum half-life, tissue distribution and activity of a given human IgG (Dall'Acqua et al…”
mentioning
confidence: 99%
“…However, studies have shown that due to the structural differences in proteins, the Fc fragment of IgY cannot bind to the Fc receptor on mammalian cell membranes. Thus, IgY does not undergo endocytosis and transport into blood by FcRn . Other studies have indicated that surface modifications of proteins by hydrophobization could improve transport.…”
Section: Discussionmentioning
confidence: 99%